Day of the dinosaurs : step into a spectacular prehistoric world - Brusatte, Stephen (Wide Eyed Editions, 2016)
Learn everything you ever wanted to know about dinosaurs in this book that allows you to compare the biggest, fastest and fiercest creatures of the land, sea and sky from four different prehistoric periods: the Triassic, the early Jurassic, the Late Jurassic and the Cretaceous. Sections on diet, weapons and defence and dinosaur senses make this a comprehensive introduction to one of the earth's most successful animals. Fact-filled, fully illustrated and in an exciting large format, this is a thrilling read for any budding paleontologist. --Publisher